Analisis Kesulitan Pelaksanaan Perkuliahan PPG Dalam Jabatan dalam Lingkup Kemendikbud - Syafitri, Ely; Nisa, Khairun; Anim, Anim; Sirait, Syahriani; Rahmadani, Elfira; Rahayu, Sri (Perkumpulan Pengelola Jurnal PAUD Indonesia, 2024)
In-Service Teacher Professional Education is a program designed to improve the quality of teachers who are already in the office or are currently actively teaching. This program is carried out online, so this program also has several difficulties faced by students. This research was conducted at Asahan University to examine the difficulties of implementing lectures. Data was collected from 85 respondents. The main obstacles faced by students include internet network problems, technical obstacles, time constraints, difficulties in understanding the material, and adapting to change. The difficulties faced by PPG Daljab students require holistic attention from educational institutions. The government and educational institutions need to respond to these findings to ensure effective and inclusive learning in the context of PPG Daljab.